The economic consequences of private lands conservation using conservation easements in Colorado - Swartzentruber, Ryan, author; Seidl, Andrew, advisor; Jablonski, Becca B. R., committee member; Pejchar, Liba, committee member (Colorado State University. Libraries, 2019)
Conservation easements have been used across the United States to preserve natural amenities and compensate landowners for the public goods they provide. From the Farm and Ranch Land Protection Program to the Grassland Reserve Program, Colorado conserves 2.4 million acres of land (Colorado Natural Heritage Program and the Geospatial Centroid, 2018) This thesis explores the economic implications of Federal conservation easements through the Agricultural Conservation Easement Program in Colorado. Using Input-Output modeling I found that conservation easements contributed $176 million to Colorado's economic activity. Further Multi-Region Input-Output models showed that conservation easements support rural counties between $106 million and $112 million more than two counterfactuals I considered: decreasing federal income tax and a zero counterfactual. Further, using benefit transfer analysis, I estimated that all conservation easements in Colorado provide between $40 and $47 billion in ecosystem service benefits to Coloradoans. Using econometric meta-analysis techniques, I estimated that Coloradoans are willing to pay $4.3 billion for all the conserved lands in Colorado. I propose an alternative payment methodology which incentivizes landowners to enroll environmentally important lands rather than using development opportunity costs to determine payments.
Keywords: conservation easement